Inflammatory responses to a pathogenic West Nile virus strain - Huang, Bixing (BMC Infect Dis, 2019)
BACKGROUND: West Nile virus (WNV) circulates across Australia and was referred to historically as Kunjin virus (WNV(KUN)). WNV(KUN) has been considered more benign than other WNV strains circulating globally. In 2011, a more virulent form of the virus emerged during an outbreak of equine arboviral disease in Australia. METHODS: To better understand the emergence of this virulent phenotype and the mechanism by which pathogenicity is manifested in its host, cells were infected with either the virulent strain (NSW2012), or less pathogenic historical isolates, and their innate immune responses compared by digital immune gene expression profiling. Two different cell systems were used: a neuroblastoma cell line (SK-N-SH cells) and neuronal cells derived from induced pluripotent stem cells (iPSCs). RESULTS: Significant innate immune gene induction was observed in both systems. The NSW2012 isolate induced higher gene expression of two genes (IL-8 and CCL2) when compared with cells infected with less pathogenic isolates. Pathway analysis of induced inflammation-associated genes also indicated generally higher activation in infected NSW2012 cells. However, this differential response was not paralleled in the neuronal cultures. CONCLUSION: NSW2012 may have unique genetic characteristics which contributed to the outbreak. The data herein is consistent with the possibility that the virulence of NSW2012 is underpinned by increased induction of inflammatory genes.